2021
DOI: 10.1007/s40264-021-01120-9
|View full text |Cite
|
Sign up to set email alerts
|

Repeated or Continuous Medically Supervised Ketamine Administration Associated with Hepatobiliary Adverse Events: A Retrospective Case Series

Abstract: Introduction Emerging off-label medical uses of ketamine for the treatment of persistent conditions such as depression and chronic pain often require repeated administration. Cases reported by other countries suggest that long-term and repeated exposure to ketamine may be associated with several risks, including but not limited to hepatobiliary damage. Objective We aimed (1) to characterize the association between repeated administration of ketamine for off-label medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…In a retrospective case series analysis combined to medical literature data, Cotter et al . reported an association between repeated or continuous administration of ketamine and adverse hepatobiliary events ranging from reversible asymptomatic elevation in both serum liver aminotransferases and ALP to the development of permanent structural changes including cirrhosis and pericholeductal fibrosis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective case series analysis combined to medical literature data, Cotter et al . reported an association between repeated or continuous administration of ketamine and adverse hepatobiliary events ranging from reversible asymptomatic elevation in both serum liver aminotransferases and ALP to the development of permanent structural changes including cirrhosis and pericholeductal fibrosis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[59,61] However, the repeated use of ketamine for chronic pain management and recreational purposes has been associated with severe hepatobiliary, bladder and urinary tract toxicity. [60,62] Since most sedatives lack analgesic properties except for ketamine, opioids with potent analgesic efficacy are the cornerstone of perioperative pain management. [63] By activating central and peripheral μ opioid receptors (MORs), opioids inhibit the reflexive and emotional processing of neutron toward pain and exert analgesic effects.…”
Section: Intravenous Anesthetics and Related Toxicitymentioning
confidence: 99%
“…[ 59 , 61 ] However, the repeated use of ketamine for chronic pain management and recreational purposes has been associated with severe hepatobiliary, bladder and urinary tract toxicity. [ 60 , 62 ]…”
Section: Modern Anesthesia and Related Toxicitymentioning
confidence: 99%
“…3 Chronic ketamine use can produce numerous adverse effects including abdominal pain, LFT elevation, bile duct abnormalities, lower urinary dysfunction. 2,[4][5][6] The cholangiopathy is a chronic liver diseases associated with cholangiocyte. 7 And ketamineinduced cholangiopathy is a clinical diagnosis, in which a chronic ketamine user develops LFT elevation along with bile duct abnormalities.…”
mentioning
confidence: 99%
“…Previous studies have reported that ketamine cessation usually leads to complete resolution of LFT elevation. 3,4 Additionally, in most cases, slow reversal of biliary stricture is also occurs. 2 Therefore, ketamine cessation is the main treatment option for ketamine-induced cholangiopathy.…”
mentioning
confidence: 99%